Sense and sensibility - Austen, Jane, 1775-1817 (Vintage Classics, 2007)
Two sisters could hardly be more different. Elinor Dashwood, an architecture student, values discretion above all. Her impulsive sister Marianne displays her creativity everywhere as she dreams of going to art school. But when the family finds itself forced out of Norland Park, their beloved home for twenty years, their values are severely put to the test. Can Elinor remain stoic knowing that the man she likes has been ensnared by another girl? Will Marianne's faith in love be shaken by meeting the hottest boy in the county? And when social media is the controlling force at play, can love ever triumph over conventions and disapproval?